EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON PERFORMANCE OF BUREAU OF HUMAN RESOURCES OF THE POLDA METRO JAYA EMPLOYEES WITH WORK ENVIRONMENT AS INTERVENING VARIABLE - Suyukoh, Hanafi; Djamil Mz, Masydzulhak; Badawi Saluy, Ahmad (Dinasti Publisher, 2021)
This study aims to determine the effect of work motivation and work discipline on employee performance mediated by the work environment. The number of respondents involved in this study were 55 respondents, all respondents were employees of the Bureau of Human Resources Polda Metro Jaya. This study uses a quantitative approach. The data in this study are primary data obtained from the results of distributing questionnaires. The collected research data were then analyzed using the Partial Least Square (PLS) analysis technique with the help of the Smartpls program. Based on the results of the analysis in this study, it was found that Work Motivation, Work Discipline and Work Environment have a positive effect on performance, Work Motivation and Work Discipline have a positive effect on the Work Environment, Work environment can mediate the indirect effect of Work Motivation and Work Discipline on performance.